Effects of Oxygen Vacancies in a Zinc Oxide Electron Transport Layer on Long-Term Degradation and Short-Term Photo-Induced Changes in the Operation Characteristics of Organic Solar Cells - Ryu, Shin Young; Ha, Na Young; Ahn, Yeong Hwan; Park, Ji Yong; Lee, Soonil (ACS Applied Energy Materials, 2022)
We studied changes in current density-voltage (J-V) characteristics of organic solar cells (OSCs) with a ZnO electron-transport layer (ETL) with respect to illumination intensity and aging time. Unlike an encapsulated OSC that remained almost intact up to 195 h, an unsealed OSC showed steady degradation. To elucidate the origin of long-term degradation, we carried out systematic simulations and identified six parameters that were responsible for aging effects in dark J-V curves. Among these six parameters, additional adjustments were necessary only for donor density and energy-barrier height, both of which were linked to a ZnO ETL, to reproduce a set of J-V curves concomitantly measured at 12 illumination conditions. We note that oxygen vacancies in ZnO behave as electron donors and, additionally, result in dipole-moment losses. Consequently, reoxidation of a ZnO ETL resulted from slow diffusion of ambient oxygen or water, lowered the electron quasi-Fermi level, and increased the energy-barrier height. On the contrary, light-induced generation of oxygen vacancies, a short-term effect that disappears after turning illumination off, shifted the electron quasi-Fermi level upward and decreased the energy-barrier height. Because light-induced effects counteracted those of long-term reoxidation, light intensity-dependent variations in J-V curves became more prominent with aging.
Keywords: Effect of oxygen; Electron transport layers; Energy barrier height; J-V characteristics; Long-term degradation; Operation characteristic; Photoinduced change; Photoinduced effects; Quasi-Fermi level; Re-oxidation; long-term degradation; organic solar cell; oxygen vacancy; photo-induced effects; zinc oxide